2003
DOI: 10.1002/ps.736
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of 3‐hydroxy‐3‐methylglutaryl‐CoA reductase lower fecundity in the German cockroach: correlation between the effects on fecundity in vivo with the inhibition of enzymatic activity in embryo cells

Abstract: The enzyme 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase is crucial to insect development and reproduction, as revealed by the sterilising properties of some specific inhibitors of it. In the present paper, we study the sterilising effects of a number of HMG-CoA reductase inhibitors on the German cockroach, Blattella germanica (L). The inhibitors tested were naringenin, lovastatin, mevastatin, simvastatin, atorvastatin and fluvastatin. The first two compounds were ineffective or scarcely effective as HMG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Over the past decade, researchers have discovered that HMGR may have various essential roles in the regulation of embryonic development, induction of vitellogenin synthesis and pheromone production in insects. For example, the regulatory role of HMGR has been widely investigated in cockroach species, including Blattella germanica and Diploptera punctata [12], [13]. Studies have shown that inhibitors of HMGR can prevent the synthesis of vitellogenin [14], [15] and can also reduce the fecundity of B. germanica .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, researchers have discovered that HMGR may have various essential roles in the regulation of embryonic development, induction of vitellogenin synthesis and pheromone production in insects. For example, the regulatory role of HMGR has been widely investigated in cockroach species, including Blattella germanica and Diploptera punctata [12], [13]. Studies have shown that inhibitors of HMGR can prevent the synthesis of vitellogenin [14], [15] and can also reduce the fecundity of B. germanica .…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the two isomers in each column bearing the same aryl substitutions showed that the ( Z )‐isomers are consistently more active across the two species, often demonstrating > 80% control of both S. exigua and T. ni at the two doses. The 4‐fluoro‐3‐methylphenyl A ring (X 1 = H, X 2 = F, X 3 = CH 3 ) that was present in the original literature compound 1 demonstrated activity with both E/Z‐ isomers; however, the ( E )‐isomers 7a , 7g , 7n and 7o resulted in numerically lower mortality at the 50 μg cm −2 dose and little to no mortality at the lower doses. Changing the fluorine on the A ring to a chlorine (X 2 = Cl) led to very potent activity of the ( Z )‐2‐arylstilbenes 7c , 7h , 7j and 7l , but the corresponding ( E )‐stilbenes of these analogs were considerably less active on both species.…”
Section: Resultsmentioning
confidence: 99%
“…A common approach for the discovery of new agrochemical screening hits is chemical scaffold hopping, which creates new opportunities by incorporating novel scaffolds into known molecules from the literature that have demonstrated biological potency . 3‐Hydroxyl‐3‐methylglutaryl‐CoA (HMG CoA) reductase inhibitors have been studied in lepidopteran species and cockroaches as insecticides, because HMG‐CoA reductase is the enzyme responsible for the conversion of HMG‐CoA to mevalonic acid, the precursor of isoprenoid groups in the production of juvenile hormones in insects . Inhibition of this enzyme could lead to a new insecticide, as inhibitors of juvenile hormones have been investigated as potential insecticides and juvenile hormone mimics are already commercially available for insect control …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, these studies are not conclusive due to ascertainment bias: (i) in some cases pregnant women took potentially teratogenic drugs other than statins [Trakadis et al, 2009] or (ii) previous maternal health disorders like prepregnancy diabetes, obesity or both [Petersen et al, 2008] or (iii) the small number of cases identified enables the validation of a stastically significant conclusion [Edison & Muenke, 2004, 2005Petersen et al, 2008]. Furthermore, none of the studies evaluated the possibility of decreased fertility, increased pre-implantation or peri-implantation losses that could be increased as shown in animal experiments [Elkin & Yan , 1999;Lee et al, 2007;Ohashi et al, 2003;Richards & Cole, 2006;Zapata et al, 2003]. …”
Section: Statinsmentioning
confidence: 99%